Effect of laser shock peening on ratcheting strain accumulation, fatigue life and bulk texture evolution in HSLA steel. (October 2022) - Dwivedi, Pushpendra Kumar; Vinjamuri, R.; Rai, Arun Kumar; Ganesh, P.; Ranganathan, K.; Bindra, K.S.; Dutta, Krishna
Highlights: Uniaxial ratcheting tests were done on as-received/laser shock peened HSLA steel. Laser shock peening significantly improved ratcheting life of investigated HSLA steel. Compressive stress developed on peened surfaces (∼500 μm depth) with least roughness. Significant variation of texture intensity took place in peened + ratcheted specimens. Abstract: The effect of laser shock peening (LSP) on the surface properties and ratcheting behavior of a high strength low alloy (HSLA) ASTM A 588 Grade D steel was studied in this investigation. Bulk texture evolution in the unpeened and laser peened specimens was also studied using X-ray diffraction analysis. The results show that the LSP improves the surface mechanical properties significantly without much deterioration of the surface roughness. Accumulation of the ratcheting strain reduced considerably associated with enhancement of the fatigue lives: about twice, if compared with the unpeened specimens. Strengthening of 0 1 1 〈1 0 0〉 and 0 1 1 〈1 1 1〉 texture components were observed with increased ratcheting strain in both unpeened and laser peened specimens. The induced compressive residual stresses and marginal grain refinement during the LSP caused the improvement in fatigue lives of the specimens.